Indirect effects of an aid program: the case of progresa and consumption - Manuela Angelucci; Giacomo De Giorgi (Institute for the Study of Labor (IZA), 2006)
Aid programs in developing countries are likely to affect all households living in the treated areas, both eligible and non-eligible ones. Studies that focus on the treatment effect on the treated may fail to capture important spillover effects. We exploit the unique design of an aid program's experimental trial to identify its indirect effect on consumption for non-eligible households living in treated areas. We find that this effect is positive, and that it occurs through changes in the insurance and credit markets: non-eligible households receive more transfers, and borrow more when hit by a negative idiosyncratic shock, because of the program liquidity injection, thus they can reduce their precautionary savings. We also test for general equilibrium effects in the local labor and goods markets, finding no significant changes in labor income and prices, while there is a reduction in earnings from sales of agricultural products, which are now consumed. We show that this class of aid programs has important positive externalities, thus their overall effect is larger than the effect on the treated. Our results confirm that a key identifying assumption - that the treatment has no effect on the non-treated - is likely to be violated in similar policy designs.
Keywords: E21; H43; I38; O12; O17; 330; program evaluation; consumption; Progresa